A new method to determine laterality of mobile telephone use in adolescents. Issue 8 (2nd December 2009) - Inyang, Imo; Benke, Geza; McKenzie, Ray; Wolfe, Rory; Abramson, Michael J
Abstract : Objectives: As more children use mobile (cellular) telephones, public anxiety grows about the possible adverse health effects of radiofrequency (RF) exposure upon developing nervous systems. Most epidemiological studies investigating the health effects of mobile telephones have relied on self-reports from questionnaires. While there are some validation studies investigating the accuracy of self-reported mobile phone use in adults and adolescents, self-reported laterality of use has not been validated at any age. Although this study mainly sought to validate the accuracy of self-reported laterality of mobile telephone use in adolescents, investigation also covered number and duration of calls. Methods: We monitored 455 calls in 30 students, mean age (SD) 14 (0.4) years. For 1 week, participants used hardware modified phones (HMPs) which logged dosimetric parameters such as laterality (side of head), date, number and duration of calls. These 'gold standard' measurements were compared with questionnaire self-reported laterality and estimated typical weekly phone use. Results: Agreement between HMPs and self-reported laterality was modest (κ=0.3, 95% CI 0.0 to 0.6). Concordance between HMP measured and self-reported number of calls was fair (intraclass correlation coefficient (ICC)=0.38, 95% CI 0.07 to 0.69), but poor for duration (ICC=0.01, 95% CI 0.00 to 0.37) with wide limits of agreement for both. Conclusions: These results suggest that adolescent self-reported laterality was of limited validity. Adolescent self-reported phone use by number and duration of calls was generally inaccurate but comparable to recent adult studies. Epidemiological studies of mobile phone use based on self-reported information may underestimate true associations with health effects.